Identification of Bacteria Aeromonas Hydrophila in The Fish Comodites Transported to Sumatera Island Through Port of Merak – Banten - Ishaaq Saputra; Forcep Rio Indaryanto (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Aeromonas hydrophila is one of the pathogenic bacteria existed in Indonesia and have negative impact on aquaculture. The high mobility of transported fish commodities through Merak Port also increases the potential fish diseases outbreak carried from Java to Sumatera Island, included A.hydrophila bacteria. The aim of this research was to evaluate the frequency of A.hydrophila found in fish transported through Merak Port. This research was done by collecting data series from 2014 to 2016 at Fish Quarantine and Inspection Agency of Merak. Results indicated that A. hydrophila dominate among other bacteria (31.37%). However, trend of this bacteria decreased by the time with up to 56.9%. This results can be used as the basic information of prevention tool/mitigation action to prevent the Motile Aeromonas Septicemia (MAS) disease outbreak caused by A. hydrophila.